Work Stress on Turnover Intention in Media Companies in Bandung City - Budiarti, Isniar; Nurfatimah, Maya (International Journal of Entrepreneurship & Technopreneur (INJETECH), 2025)
This study aims to determine the extent to which stress at work affects turnover intention in one of the media companies in Bandung. This study used a sample of 30 respondents from a media company in Bandung. The sample method used in this study is non-probability sampling, with data collected using questionnaires, surveys, and observations. The method used in this study is simple linear regression analysis, which is then carried out using SPSS 20 for Windows. The results of stress at work have a positive and significant impact on turnover intention in one of the media companies in Bandung. The higher the level of work stress that employees feel, the greater their desire to leave the company. Because of this, media companies must consider employee work conditions in order to reduce work stress and reduce turnover intention.